2011
DOI: 10.1071/as11025
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Spectroscopy and Spectropolarimetry of Some Late F- / Early G-type Sun-like Stars as Targets for Zeeman Doppler Imaging

Abstract: High-resolution spectroscopy and spectropolarimetry have been undertaken at the AngloAustralian Telescope in order to identify suitable targets for magnetic studies of young Sun-like stars, for the proxy study of early solar evolution. This study involved the investigation of some variable late F-/ early G-type Sun-like stars originally identified by the Hipparcos mission. Of the 38 stars observed for this study, HIP 31021, HIP 64732, HIP 73780 were found to be spectroscopic binary stars, while HIP 19072, HIP … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
4
10
1
Order By: Relevance
“…Indication of binarity comes also from the astrometric acceleration detected by Hipparcos. The small v sin i quoted by Nordström et al (2004) (2 km s −1 ) is highly discrepant with the fast rotation reported by Waite et al (2011) and with our own spectrum (70 km s −1 ). The Nordström et al (2004) RV measurement should therefore be taken with caution.…”
Section: Hip 36948 = Hd 61005contrasting
confidence: 52%
See 3 more Smart Citations
“…Indication of binarity comes also from the astrometric acceleration detected by Hipparcos. The small v sin i quoted by Nordström et al (2004) (2 km s −1 ) is highly discrepant with the fast rotation reported by Waite et al (2011) and with our own spectrum (70 km s −1 ). The Nordström et al (2004) RV measurement should therefore be taken with caution.…”
Section: Hip 36948 = Hd 61005contrasting
confidence: 52%
“…However, the deformation of the line profile might also be due to spots. This issue was also discussed by Waite et al (2011), who favor the star-spot interpretation. We therefore consider this star as only a possible binary.…”
Section: Hip 36948 = Hd 61005mentioning
confidence: 88%
See 2 more Smart Citations
“…Bains et al 2009;Robertson et al 2010;Waite et al 2011) would have all contributed to those papers, while the lead-author will have likely performed the bulk of the work. Figure 3 shows the normalized citation count (a sorting option within ADS in which each article's total citation count is divided by the number of contributing authors), and an individuals total citation count when they are the lead-author (achieved by placing the carat symbol,^, in front of an author's name within the ADS web-form).…”
Section: The Citation Datamentioning
confidence: 99%